EVALUATION OF COFFEE GROWTH, YIELD AND QUALITY UNDER COFFEE SHADE TREES AT MECHARA ON STATION, WEST HARARGHE ZONE, ETHIOPIA - Roba, Alemayehu Diriba; Dekeba, Shimelis; Gizaw, Wasihun; Mezigebu, Mosisa (International Journal of Research -GRANTHAALAYAH, 2021)
Abstract: Coffee production with shade trees is important to improve growth and quality of coffee, sustain and restore agroecology and nature based agroforestry practices. The trial was conducted at Mechara Agricultural Research Center (on station) in DaroLebu District of West Hararghe Zone, Oromia, Ethiopia. The study was intended to evaluate the influence of coffee shade trees on growth performance, yield and quality of coffee (Coffea arabica L.) under the canopy of Erytherina absinica, Cordia africana and Acacia sieberiana. The design was Randomized complete block design with three replications. The outcome had been observed a significant value at (p<0.05) probability level, non- significant value at (p>0.05) probability level and highly significance value at (p<0.01) probability level between treatments. Statistically significant and non- significant differences were observed between shaded and unshaded as well as within shaded effect based on the given parameters. Integration of shade in coffee farming system created creditable promising in producing organic coffee. Shade utility could be confirmed as to be ecologically sustainable, economically viable and socially acceptable practice. In so doing that, the effect of Erytherina absinica, Cordia africana shade trees illustrated the highest mean value in most parameters, while the least one is under the Acacia sieberiana shade tree. So the effect of Erytherina absinica mean observed with the highest value on total bearing plants 60%, thousand seed weight 59% and yield in Quintal per hectare 47.4% greater than the least treatments’ mean value based on growth parameters. On the other hand, the effect of Erytherina absinica mean observed with the higher value on aromatic intensity 46.4%, aromatic quality 87.2%, acidity 92.4%, body 93.5%, flavors 88.6% and overall quality 88.6% than the least treatments’ mean value, and also the effect of un-shade mean observed with the higher value on astringency 68.8% and bitterness 93.5% than the least treatments’ mean value based on organoleptic parameters. The highest mean value of Erytherina absinica observed on total bearing plants 12.1, thousand seed weight 130 gram and yield in Quintal per hectare 5.7 based on growth parameters, while based on organoleptic parameters, the highest mean value observed under the effect of Erytherina absinica shade tree on aromatic intensity 4.5, aromatic quality 3.9, acidity 7.9, body 7.7, flavors 7.9 and overall quality 7.9. Therefore, based on the most treatments’ parameters, to be the best shade tree was Erythrina abyssinica followed by cordia africana. Commonly, the dynamic indication of the treatment’s means difference were indicated between shaded and unshaded rather than within shaded means variation at most treatments’ parameters.